(untitled) (Revista NUPEART, 2024)
This article aims to understand silence as a gesture in the musical work 4′33″, composed by John Cage (1952). Theoretical references were taken from Galard (2008) and Flusser (2014) for a relevant understanding of the concept of gesture, which aimed to culminate in the meaning of the contemporary philosopher Agamben (2018). The musical discussion was observed through Durão (2005) and Zagonel (2007), as well as technical references pertinent to understanding the theme. In addition to the literature review, the methodology used a qualitative approach, which allowed for an appreciation of the gesture, characterizing it as an act or (im)posture, deviant from everyday life, which has both aesthetic and political dimensions. It was concluded that 4′33″ is a gesture against passive listening, co-opted by the contextualized logics of an immediate and predictable culture, given that the musical work itself suggests the resignification and understanding of silence, promoting active and reflective listening.